2016
DOI: 10.1002/nau.23183
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pulsed-radiofrequency neuromodulation on the rat with overactive bladder

Abstract: PRF electrical stimulation of pelvic nerves exerted a long-lasting effect of suppressing AA-induced detrusor overactivity. This modality can be used as an alternative approach for improving bladder continence in patients with overactive bladder syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…In the clinical setting, sacral nerve stimulation is the procedure offered most commonly in cases that are refractory to current pharmacological and chemodenervation approaches, although other targets are also being used (see Janssen et al, 2017 for a recent review). In animal studies the net has been cast wider and there are several indications from studies in anesthetized cats and rats that stimulation of the tibial, saphenous, pudendal, dorsal penile, dorsal clitoral, and pelvic nerves all have the potential to modulate voiding ( Snellings and Grill, 2012 ; Su et al, 2012a , b ; Kovacevic and Yoo, 2014 ; Jen et al, 2016 ; Langdale et al, 2017 ; Moazzam and Yoo, 2017 ; Uy et al, 2017 ). In these studies, nerve stimulation was able to inhibit or reduce the frequency of voiding, or to decrease the rate of micturition-like contractions produced under isovolumetric conditions by producing an increase in bladder capacity.…”
Section: Introductionmentioning
confidence: 99%
“…In the clinical setting, sacral nerve stimulation is the procedure offered most commonly in cases that are refractory to current pharmacological and chemodenervation approaches, although other targets are also being used (see Janssen et al, 2017 for a recent review). In animal studies the net has been cast wider and there are several indications from studies in anesthetized cats and rats that stimulation of the tibial, saphenous, pudendal, dorsal penile, dorsal clitoral, and pelvic nerves all have the potential to modulate voiding ( Snellings and Grill, 2012 ; Su et al, 2012a , b ; Kovacevic and Yoo, 2014 ; Jen et al, 2016 ; Langdale et al, 2017 ; Moazzam and Yoo, 2017 ; Uy et al, 2017 ). In these studies, nerve stimulation was able to inhibit or reduce the frequency of voiding, or to decrease the rate of micturition-like contractions produced under isovolumetric conditions by producing an increase in bladder capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant animal studies have shown that RF treatment reduces bladder nerve density without evidence of lasting epithelial injury ( 24 ). RF electrical stimulation of pelvic nerves has a long-lasting inhibitory effect on the 0.5% acetic acid-induced detrusor overactivity rat model without causing significant nerve injury ( 25 ). There is one study that reported long-term improvement in pain and symptoms associated with interstitial cystitis in patients after RF treatment of the superior hypogastric plexus ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…At even higher frequencies, pulsed radiofrequency stimulation has also been shown to have the potential for modulating voiding. A 5‐minute period of short (80 ms) pulses at 500 kHz delivered to the pelvic nerve at 2 Hz was able to reverse the decrease in bladder capacity and reduce the frequency of bladder contraction in a rat model of cystitis . The effects of the 5‐minute period of stimulation lasted for at least 3.5 hours and appeared to be selective for pelvic nerve afferents (equivalent stimulation of the pudendal nerve had no effect) and importantly, did not induce nerve damage.…”
Section: Can Recent Advances In Understanding the Mechanism Of Action...mentioning
confidence: 94%